RETROSPECTIVE ANALYSIS OF ADRENAL VEIN SAMPLING (AVS) SUCCESS: A STUDY OF A MALAYSIAN COHORT FROM A SINGLE TERTIARY CENTER - Nazri, SK Syed Mohammed; Zakaria, R; Sukor, N; Azizan, EA (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Adrenal venous sampling (AVS) is the current gold standard to properly lateralise primary aldosteronism (PA) caused by an adrenal lesion. A successful AVS can help to identify unilateral PA giving the option of an adrenalectomy of the affected adrenal as a one-off treatment instead of lifelong medication. However, due to the invasive nature of the technique and the difficulty in identifying, cannulating, and withdrawing blood from the adrenal vein, AVS is not always successful. Herein, we aim to elucidate the clinical and laboratory characteristics associated with successful AVS in patients with PA. METHODOLOGY 100 AVS procedures conducted at Hospital Universiti Kebangsaan Malaysia (HUKM), Kuala Lumpur, Malaysia between 2017 and 2020 were analysed retrospectively. Success of AVS, sociodemography, and blood results of the patients pre-adrenalectomy were collected and compared. The variables investigated were age, gender, race, duration of hypertension, body mass index, aldosterone, serum sodium, serum potassium, and hypokalemia. RESULTS Of the 100 AVS procedures studied, 54 were performed on men and 46 were on women. Malay patients presented the highest frequency of patients (n=53) followed by Chinese (n=47). AVS was most frequently performed in patients aged 36-45 years (n=38) followed by 26-35 years (n=20), 56- 65 years (n=16), 46-55 years (n=15), 66-75 years (6 patients), 16-25 years (4 patients) and 76-85 years (1 patient). AVS was successful in sixty-three patients, but was unsuccessful in thirty seven patients. Variables significantly associated with successful AVS were Malay ethnicity (p=0.048) and high serum sodium levels (p=0.019). CONCLUSION Successful AVS in patients with PA was most significantly associated with Malay ethnicity and high serum sodium. There were no significant associations found for age, gender, duration of hypertension, body mass index, aldosterone, and potassium levels.